The Novel Dual GIP and GLP‐1 Receptor Agonist Tirzepatide Attenuates Colon Cancer Development by Regulating Glucose Metabolism - Yikai Zhang; Yi Xie; Shenglong Xia; Xinnuo Ge; Jiaying Li; Fang Liu; Fan Jia; Shengyao Wang; Qiao Zhou; Menghan Gao; Weihuan Fang; Chao Zheng (Advanced Science)
Abstract Colorectal cancer (CRC) is a leading cause of cancer mortality while diabetes is a recognized risk factor for CRC. Here we report that tirzepatide (TZP), a novel polypeptide/glucagon‐like peptide 1 receptor (GIPR/GLP‐1R) agonist for the treatment of diabetes, has a role in attenuating CRC growth. TZP significantly inhibited colon cancer cell proliferation promoted apoptosis in vitro and induced durable tumor regression in vivo under hyperglycemic and nonhyperglycemic conditions across multiple murine cancer models. As glucose metabolism is known to critically regulate colon cancer progression, spatial metabolomics results revealed that glucose metabolites are robustly reduced in the colon cancer regions of the TZP‐treated mice. TZP inhibited glucose uptake and destabilized hypoxia‐inducible factor‐1 alpha (HIF‐1α) with reduced expression and activity of the rate‐limiting enzymes 6‐phosphofructo‐2‐kinase/fructose‐2,6‐bisphosphatase 3 (PFKFB3) and phosphofructokinase 1 (PFK‐1). These effects contributed to the downregulation of glycolysis and the tricarboxylic acid (TCA) cycle. TZP also delayed tumor development in a patient‐derived xenograft (PDX) mouse model accompanied by HIF‐1α mediated PFKFB3‐PFK‐1 inhibition. Therefore, the study provides strong evidence that glycolysis‐blocking TZP, besides its application in treating type 2 diabetes, has the potential for preclinical studies as a therapy for colorectal cancer used either as monotherapy or in combination with other anticancer therapies.